2021
DOI: 10.3390/jmse9101048
|View full text |Cite
|
Sign up to set email alerts
|

General and Local Characteristics of Current Marine Heatwave in the Red Sea

Abstract: In the ocean, heat waves are vital climatic extremes that can destroy the ecosystem together with ensuing socioeconomic consequences. Marine heat waves (MHW) recently attracted public interest, as well as scientific researchers, which motivates us to analyze the current heat wave events over the Red Sea and its surrounding sea region (Gulf of Aden). First, a comprehensive evaluation of how the extreme Red Sea surface temperature has been changing is presented using 0.25° daily gridded optimum interpolation sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Sea, of which 590 days (58%) occurred in the last decade. These results indicate that the rapid increase in SST in the Red Sea has caused a positive trend in MHWs in the region, and they also suggest that MHWs in the Red Sea are expected to increase in the future with global warming, which is consistent with the findings of (Bawadekji et al, 2021 and. A comparison then was made between the atmospheric variables and the annual MHW frequency to provide a general idea of the atmospheric conditions associated with the years with the highest MHW occurrence for the entire RS, NRS and SRS.…”
Section: Climate Modes and Mhws In The Red Seasupporting
confidence: 88%
See 2 more Smart Citations
“…Sea, of which 590 days (58%) occurred in the last decade. These results indicate that the rapid increase in SST in the Red Sea has caused a positive trend in MHWs in the region, and they also suggest that MHWs in the Red Sea are expected to increase in the future with global warming, which is consistent with the findings of (Bawadekji et al, 2021 and. A comparison then was made between the atmospheric variables and the annual MHW frequency to provide a general idea of the atmospheric conditions associated with the years with the highest MHW occurrence for the entire RS, NRS and SRS.…”
Section: Climate Modes and Mhws In The Red Seasupporting
confidence: 88%
“…The MHWs of the NRS were longer and more intense than those of the SRS, while the MHWs of the SRS were characterized by their frequent occurrence. The same pattern of MHW distribution was also observed by (Bawadekji et al, 2021 andMohamed et al, 2021).…”
Section: Methods Of Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Using satellite sea surface temperature (SST) data from 1985 to 2015, they found that MHWs in the Red Sea can trigger coral bleaching when their SSTs exceed the 95 th percentile, when the climatological average is 30°C or higher, last for at least seven consecutive days and occur at shallow depths (< 150 m). Bawadekji et al (2021) studied the general and local characteristics of the marine heatwaves in the Red Sea. Their study concluded that the Red Sea exhibits a meridional gradient with decreasing average annual MHW intensity and MHW duration from north to south, and a meridional gradient with increasing average annual MHW frequency from north to south.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] study the recent evolution of MHWs in the Mediterranean and Red Seas, where their frequency and intensity have clearly increased in the last four decades. Finally, [10] analyzes the main characteristics of MHWs in the Red Sea.…”
mentioning
confidence: 99%